Transport Issues in Post-Soviet Central Asia - Eronen, Jarmo (Promet - Traffic&Transportation, 2012)
After the collapse of the Soviet Union the Central Asianproducers have been actively and partly successfully looking forcompensating markets. Howeve1; the transport infrastructurewas built to se1ve interests of the Soviet state. New transportCOJTidors to the west, east and south are being constructed orplanned reducing in the long run the transport costs of CentralAsian products, which still today pw1ly use traditional and longerSoviet time outlets (pipelines, railways, ports). For both economicand geopolitical reasons Central Asian states wish tofind alternative transport routes. The EU and geopolitical rivalsof Russia, the USA and China, are helping in this, also Iran hasvested interests in the issue. Still long haulage remain a constantproblem for landlocked Central Asia and the high cost ofmany projects planned (Transcaspian or Chinese pipelines) islikely to postpone them to a distant future.